1993
DOI: 10.1136/gut.34.12.1666
|View full text |Cite
|
Sign up to set email alerts
|

Perforated peptic ulcer over 56 years. Time trends in patients and disease characteristics.

Abstract: Perforated gastroduodenal ulcer was studied in 1483 patients in the Bergen area during the years 1935-90 to discover time trends in age and sex, disease characteristics, treatment, and outcome. The male:female ratio feli from 10:1 to 1*5:1, median age increased from 41 to 62 years. Most perforations were found in the duodenum in 1935-64, and in the pyloric and praepyloric area in . There was a 10% occurrence of gastric ulcers throughout the study period. Ulcer site was related to age (more gastric and less duo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
1
6

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 20 publications
9
67
1
6
Order By: Relevance
“…Perforation has been found to be a major complication of PUD with a mortality rate ranging from 6 % to 31 % [6][7][8][11][12][13][14][15][16][17][18][19][20] . Age of patients with PPU has been gradually increasing over the last years [21][22][23] . In this series, an age >65 years tended to be associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perforation has been found to be a major complication of PUD with a mortality rate ranging from 6 % to 31 % [6][7][8][11][12][13][14][15][16][17][18][19][20] . Age of patients with PPU has been gradually increasing over the last years [21][22][23] . In this series, an age >65 years tended to be associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Peptic ulcer perforation is a serious complication which affects almost 10 % of PUD patients. Overall, PUD accounts for more than 70 % of mortality associated with the disease [3,4] . Several potential predicting factors for perforation have been evaluated in the literature, including use of ulcerogenic drugs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeons believe that many patients can be successfully managed medically with no operation and that better outcomes can be achieved. Moreover, several studies have indicated significant side effects, including diarrhea, dumping, vomiting, and weight loss due to ulcer operations (5,6). Some others have suggested surgical management, especially simple closure (7).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative morbidity is generally infectious, with pneumonia as the most common complication (up to 30%), followed by superficial and deep surgical site infections (46,47). In the elderly, perioperative cardiovascular morbidity is increased (46,47,67).…”
Section: Managementmentioning
confidence: 99%
“…For gastric ulcers, excision of the ulcer for pathologic examination remains an important surgical tenet, to rule out the possibility of perforated gastric malignancy (36, 37, 39, 54). Formal gastric resection with reconstruction (Billroth I, Billroth II, roux-en-Y) with or without vagotomy is rarely required, and is used in less than 10% of cases (40,(45)(46)(47)51). In patients with a recent (< 12 hr) perforation with a history of chronic ulcer disease and prior failed medical therapy, a definitive ulcer operation may be indicated (55)(56)(57).…”
Section: Managementmentioning
confidence: 99%